Healthcare for Trans*gender People in Germany: Gaps, Challenges, and Perspectives - Guethlein, Nora; Grahlow, Melina; Lewis, Carolin A.; Bork, Stephan; Habel, Ute; Derntl, Birgit (Frontiers in Neuroscience, 2021)
People whose gender does not correspond to the binary gender system, i.e., trans∗gender people, face two main problems when it comes to healthcare in Germany: (1) They often suffer from general psychiatric comorbidities as well as specific and significant mental distress due to gender dysphoria, and (2) the German healthcare system lacks sufficiently educated and clinically experienced medical personnel who are able to provide specialized healthcare. Aside from transition, it often is extremely difficult for trans∗gender people to get access to and be integrated into the medical system. Stigmatization and pathologization in treatment are widespread, as are long waiting times for specialized healthcare providers who are often only accessible to those trans∗gender people willing to travel long distances. Frequently, trans∗gender people face further difficulties and barriers after transition, as some healthcare professionals fail to provide suitable care (e.g., gynecological consultation for transmen). The ICD-11 German Modification (ICD-11-GM), which should be routinely used by 2022, implements a depathologization of trans∗gender people in the medical system. This paper compares the issues related to health and healthcare of trans∗gender people in Germany with those in other European countries. We review the care offered by specialized centers with regard to treatment of and support for trans∗gender people. We conclude with specific proposals that may contribute to establish an improved, up-to-date, gender-sensitive healthcare system.